Para encontrar los comportamientos políticos... Ausencias y presencias en busca de lo social en los archivos oficiales - Regina Tapia (Nuevo mundo - Mundos Nuevos, 2012)
Considering material found in government archives as a resource for historical reconstruction, I write in this article about the methodological challenge of finding a citizen voice in them, in the way the governed established liaisons with the political powers throughout two expressions in the universe of their political culture: electoral participation and their written addresses to Congress.